Solutions of nonlinear fractional differential equations systems through an implementation of the variational iteration method - Baskonus, Haci Mehmet; Belgacem, Fethi Bin Muhammad; Bulut, Hasan (De Gruyter, 2015)
In this book chapter, the Variational Iteration Method is used to solve systems of nonlinear fractional differential equations. Implementations with two separate nonlinear fractional differential equations systems illustrate a high degree of effectiveness. In the absence of explicit analytical methods, the Variational Iterative Method turns out to be a powerful tool to understand the behavior of nonlinear fractional differential equations and systems. Numerical solutions plots are obtained for each system via the Mathematica Symbolic Algebra Software 9. © 2015 Haci Mehmet Baskonus et al.
Keywords: Fractional differential equation; Nonlinear fractional differential equation systems; Variational iterational method